2-Chloromethyl-1-Dihydroxyphosphinylpyrrolidine (2C-1DPP)에 의한 백혈병 세포주 HL-60의 분화유도 효과 - 김영미(Youg Mi Kim); 주성민(Seong Min Ju); 박준호(Jun Ho Park); 오정미(Jung Mi Oh); 이채호(Chae Ho Lee); 김은철(Eun Cheol Kim); 전병훈(Byung Hun Jeon); 김원신(Won Sin Kim) (동의생리병리학회지, 2007)
We have examined the induction of HL-60 cell differentiation by treatment of 2-chloromethyl-1-dihydroxyphosphinyl pyrrolidine(2C-1DPP), which is derivative of piperidine and pyrrolidine by ${α}-phosphoramidoakylation$ reaction. It was observed that HL-60 cell proliferation was dose- and time-dependently inhibited by treatment with 2C-1DPP. 2C-1DPP treatment caused a significant change in NBT reduction and enhanced ATRA-induced NBT reduction. Treatment of 2C-1DPP to HL-60 cells increased only CD11b expression in the cells, and also increased markedly G0/G1 stage arrest of HL-60 cells. These results can suggest that 2C-1DPP induced the differentiation of HL-60 cells to granulocytes lineage and enhanced ATRA-induced differentiation. Moreover, DNA expression levels of p27 were up-regulated during 2C-1DPP-dependent HL-60 cell differentiation. Our results suggest that 2C-1DPP have potential as a therapeutic agent in human leukemia.